The role of SERPIN citrullination in thrombosis. Issue 12 (16th December 2021) - Tilvawala, Ronak; Nemmara, Venkatesh V.; Reyes, Archie C.; Sorvillo, Nicoletta; Salinger, Ari J.; Cherpokova, Deya; Fukui, Saeko; Gutch, Sarah; Wagner, Denisa; Thompson, Paul R.
Summary: Aberrant protein citrullination is associated with many pathologies; however, the specific effects of this modification remain unknown. We have previously demonstrated that serine protease inhibitors (SERPINs) are highly citrullinated in rheumatoid arthritis (RA) patients. These citrullinated SERPINs include antithrombin, antiplasmin, and t-PAI, which regulate the coagulation and fibrinolysis cascades. Notably, citrullination eliminates their inhibitory activity. Here, we demonstrate that citrullination of antithrombin and t-PAI impairs their binding to their cognate proteases. By contrast, citrullination converts antiplasmin into a substrate. We recapitulate the effects of SERPIN citrullination using in vitro plasma clotting and fibrinolysis assays. Moreover, we show that citrullinated antithrombin and antiplasmin are increased and decreased in a deep vein thrombosis (DVT) model, accounting for how SERPIN citrullination shifts the equilibrium toward thrombus formation. These data provide a direct link between increased citrullination and the risk of thrombosis in autoimmunity and indicate that aberrant SERPIN citrullination promotes pathological thrombus formation. Graphical abstract: Highlights: Citrullinated SERPINs regulate the coagulation and fibrinolysis cascades Citrullinated antithrombin and t-PAI lose their ability to bind cognate proteases Citrullinated antiplasmin is a plasmin substrate not an inhibitor SERPIN citrullination shifts the equilibrium toward thrombus formation in DVT Abstract : Tilvawala et al. demonstrate that citrullination alters the activity of SERPINs involved in the coagulation and fibrinolysis pathways and shifts the equilibrium toward thrombus formation. These data reconcile two observations: that both protein citrullination and thrombosis are elevated in autoimmunity and that aberrant SERPIN citrullination contributes to pathological thrombus formation.